Analysis of Reviews, Brand image, and Product Quality on Purchasing Decisions for OMG Lip Cream Among UNP Kediri Students. - dwi, chandra; Leksono, Poniran Yudho (Universitas Nusantara PGRI Kediri, 2025)
Research aim: This study aims to measure or analyze the existence and absence of the influence of Review, Brand Image, and product quality partially and simultaneously on the purchase decision of OMG Lip Cream in UNP Kediri Students. Design/Methode/Approach: This study uses a quantitative approach with a non-probability sampling technique. The population of this study includes all students who have used OMG Lip Cream products, with a sample of 40 respondents who have purchased the product. The data were analyzed using classical methods, assumption tests, multiple linear regression, determination coefficients and hypothesis tests. The analysis process was carried out using the SPSSv23 application, which made it easier to process the data of this research. Research Finding: The results of this study show that reviews do not have a partial influence on the purchase decision of OMG Lip Cream products. On the other hand, brand image and product quality partially have an influence on purchasing decisions. However, simultaneously the variables of reviews, brand image, and product quality positively and significantly affect purchases. Theoretical contribution/Originality: Reviews have a significant role in increasing consumer trust in OMG Lip Cream. Positive reviews from previous users can influence the process of finding information and evaluating alternatives, ultimately driving consumer intent to make a purchase. On the other hand, product quality also plays a role in supporting purchasing decisions through marketing attributes such as brand image, which is influenced by the company's image, product, and users. Attractive aspects of product design and consistency of quality are important factors in forming a positive perception in the eyes of consumers. By offering a more diverse variety of products equipped with accurate information and maintaining superior quality, OMG Lip Cream can cater to different consumer preferences while increasing the frequency of purchases. Practitionel/Policy implication: This study provides practical implications for UNP Kediri students who use OMG Lip Cream. Research limitations: : This research only focuses on reviews, brand image, and product quality as independent variables, while purchasing decisions are set as bound variables.